2015
DOI: 10.1002/2015pa002802
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of opening the Sunda Strait on the hydrography of the eastern tropical Indian Ocean

Abstract: The advection of relatively fresh Java Sea water through the Sunda Strait is presently responsible for the low-salinity "tongue" in the eastern tropical Indian Ocean with salinities as low as 32‰. The evolution of the hydrologic conditions in the eastern tropical Indian Ocean since the last glacial period, when the Sunda shelf was exposed and any advection via the Sunda Strait was cutoff, and the degree to which these conditions were affected by the Sunda Strait opening are not known. Here we have analyzed two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 68 publications
(154 reference statements)
2
20
0
1
Order By: Relevance
“…In contrast, the more northern region such as the Okinawa and Luzon Strait (NH; Dang et al, ; Sun et al, ), as well as a record off Sumatra in the eastern Indian Ocean (Mohtadi et al, ), do not present a predominant Holocene trend as shown in Figures a and d, and in the low R 2 values (<0.14) and high p and f values. The lack of a predominant Holocene trend is consistent with lower resolution records from this same region (Mohtadi et al, ; Setiawan et al, ).…”
Section: Resultssupporting
confidence: 83%
“…In contrast, the more northern region such as the Okinawa and Luzon Strait (NH; Dang et al, ; Sun et al, ), as well as a record off Sumatra in the eastern Indian Ocean (Mohtadi et al, ), do not present a predominant Holocene trend as shown in Figures a and d, and in the low R 2 values (<0.14) and high p and f values. The lack of a predominant Holocene trend is consistent with lower resolution records from this same region (Mohtadi et al, ; Setiawan et al, ).…”
Section: Resultssupporting
confidence: 83%
“…Another factor influencing δ 18 O sw is the variability in current circulation and lateral advection of isotopic signals within the Indonesian archipelago (Dang et al, ; Gibbons et al, ; Setiawan et al, ). The pronounced decrease in δ 18 O sw in the Makassar Strait and Flores Sea during the B‐A is synchronous with the rapid sea level rise during MWP 1a at ~14.5 ka (Hanebuth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Transport across the Sunda Strait during the southeast monsoon/boreal summer (blue pathway—Figure b) ranges from 0.7 to 0.83 ± 0.20 Sv (Putri, ; Susanto et al, ), and is 0.24 ± 0.10 Sv during the northwest monsoon/boreal winter (magenta pathway—Figure b; Susanto et al, ). It is also of great importance that off the Sunda Strait and southern Java is the center of the eastern pole of the Indian Ocean Dipole (10°S to 0°N and 90°E to 110°E), and during positive Indian Ocean Dipole events, low salinity water from the Java Sea significantly affects sea surface temperature and upwelling along the southern coast of Java‐Sumatra (Saji et al, ; Setiawan et al, ; Susanto et al, ; Xu et al, ; Xue et al, ).…”
Section: Methodsmentioning
confidence: 99%